JAMA’AH TABLIGH DAN PENGUATAN RELIJI DI MASYARAKAT - Ibrahim Latepo (Komunitas Dosen Dakwah Institut Agama Islam Negeri (IAIN) Palu, 2016)
Islamic preaching in society is regarded as an effort to change society into a better condition. This is carried out by positioning human beings as both subject and object of preaching. Therefore, both approach and method are necessary to be paid attention to them. Preaching should be carried out using persuasive methods based on wisdom and polite communication. Preaching with persuasive approach is one of the preaching models that strengthen Islam in society, in the context of building a happy family. One of the religious movement that makes that effort is Jama’ah Tabligh in Palu.